OPTIMALISASI SISTEM INFORMASI KEUANGAN BERBASIS WEBSITE UNTUK MENINGKATKAN TRANSPARANSI CROWDFUNDING DI SMK BAKTI KARYA PARIGI - Aziz, Nur; Prayoga, Hade Yustika (Program Studi Manajemen Pendidikan Islam, 2025)
This study aims to analyze the optimization of a web-based information system as a tool to enhance budget transparency for donor funding (crowdfunding) at SMK Bakti Karya Parigi. The main focus is to evaluate the effectiveness of the current system and provide recommendations for improving its functionality. This research uses a qualitative descriptive approach with a case study method. Data were collected through interviews with key informants, including financial managers and system developers, direct observations of the web-based information system, and analysis of relevant documents. The data were analyzed using the Miles, Huberman & Saldana (2014) model, which includes data condensation, data display, and conclusion drawing/verification. The findings indicate that the current website information system has supported budget transparency; however, several weaknesses remain, such as limited real-time data updates, a less user-friendly interface, and inadequate outreach to donors. Recommendations include improving automated financial reporting features, redesigning the user interface, and strengthening training programs for system users. The implication is that optimizing the website information system can increase donor trust in fund management at SMK Bakti Karya Parigi. Furthermore, it contributes to more accountable and sustainable educational practices.